The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ijc.30918
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mitochondrial stress 70 protein/mortalin and cytosolic Hsp70 in blood: Risk indicators in colorectal cancer

Abstract: Mitochondrial mortalin and cytosolic Hsp70 are essential chaperones overexpressed in cancer cells. Our goals were to reproduce our earlier findings of elevated circulating levels of mortalin and Hsp70 in colorectal cancer (CRC) patients with a larger patient cohort, to compare death risk assessment of mortalin, Hsp70, CEA and C19-9 and to assess their prognostic value in various CRC stages. Mortalin, Hsp70, CEA and CA19-9 levels were determined in sera of 235 CRC patients enrolled in the study and followed up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
2
20
1
Order By: Relevance
“…Apart from AIFM3, several mitochondrial proteins such as mitochondrial ribosomal protein, mitochondrial stress 70 protein (mortalin), pyruvate dehydrogenase kinase 3, and manganese superoxide dismutase have been detected in the serum, and has been used as serum marker for breast cancer, colorectal cancer, CCA, and ovarian cancer [ 20 , 21 , 22 , 23 ] The present results suggest that AIFM3 should be added as a mitochondrial protein marker in the sera of patients with CCA and probably other cancers. In the present study, serum AIFM3 level in the CCA patients group was significantly ( p < 0.0001) higher than that of HC.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from AIFM3, several mitochondrial proteins such as mitochondrial ribosomal protein, mitochondrial stress 70 protein (mortalin), pyruvate dehydrogenase kinase 3, and manganese superoxide dismutase have been detected in the serum, and has been used as serum marker for breast cancer, colorectal cancer, CCA, and ovarian cancer [ 20 , 21 , 22 , 23 ] The present results suggest that AIFM3 should be added as a mitochondrial protein marker in the sera of patients with CCA and probably other cancers. In the present study, serum AIFM3 level in the CCA patients group was significantly ( p < 0.0001) higher than that of HC.…”
Section: Discussionmentioning
confidence: 99%
“…GRP75 (also known as Hsp70 or mortalin) plays a major role in the import and refolding of mitochondrial proteins, representing a potential serum biomarker of high prognostic value for patients with colorectal cancer (276). Additionally, Cruz et al demonstrated that this protein is a candidate biomarker of drug-resistant disease in ovarian cancer cell lines and tissues (277), while Niu et al described its involvement in modulating oncogenic Dbl-driven endocytosis (278).…”
Section: Mitochondrion and Nucleusmentioning
confidence: 99%
“…The highly conserved member of the 70 kDa heat shock protein family Hsp70 is considered as a DAMP when released as a free molecule by dying cancer cells [11] whereas exosomal Hsp70 (exHsp70) which is actively released by viable tumor cells serves as a marker for viable tumor mass [12, 13]. Elevated exHsp70 serum levels as detected by the lipHsp70 ELISA [14] that detects both, free and exosomal Hsp70 have been found in breast cancer patients [15], patients with hepatocellular carcinoma, lung cancer [16], colorectal carcinoma [17, 18] and other cancer entities [19]. Although high exHsp70 levels are generally associated with an adverse prognosis also in breast cancer patients [20, 21], less is known about the role of free Hsp70 as a predictive marker for therapy response.…”
Section: Introductionmentioning
confidence: 99%